For a dialectic of planning pasts and futures: Theoretical courses and recourses in conversation with Patsy Healey - Tulumello, Simone (AESOP, 2025)
This reflective essay revisits the intellectual legacy of planning theory by engaging with past debates and reconnecting them with contemporary concerns. Drawing inspiration from a concluding paragraph drafted by Patsy Healey for plaNext Volume 3, the author explores how new generations of planning scholars can better understand the historical trajectories of concepts such as system thinking, resilience, and transnational flows of planning ideas. The article reconstructs the origins of the 9th AESOP Young Academics Conference (Palermo, 2015) and analyses its thematic emphasis on geographical differences, postcolonial critique, and the blind spots between micro-practices and broader urban trends. It highlights how issues once considered marginal—such as Western-centrism, uneven development, and the politics of knowledge transfer—have since become central in planning theory. The essay then examines how planning scholars engage with concepts of time, challenging linear narratives of progress. Drawing on critical theory, political economy, and abolitionist thought, the author argues for a dialectical understanding of planning futures: not as predetermined visions to be implemented, but as emergent possibilities already present in the struggles, contradictions, and unrealised alternatives within the contemporary urban condition.
plaNext – Next Generation Planning, 15 (2025)
Keywords: planning theory; planning futures; dialectics; Patsy Healey; temporalities; critical planning